2011
DOI: 10.1097/pcc.0b013e3181ff41c1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a collaborative program to provide extracorporeal membrane oxygenation for adults with refractory hypoxemia within the framework of a pandemic*

Abstract: In the setting of the pH1N1 influenza pandemic, an adult respiratory extracorporeal membrane oxygenation program was successfully developed to complement an established neonatal-pediatric program. This program expansion integrated all of the necessary components involved in the development process from start to finish and confirms that a healthcare system can respond very quickly and successfully to an urgent healthcare need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…With simplification of ECMO technology we may no longer need 1:1 nurse/ECMO-specialist-to-patient ratio, which would improve resource allocation. 78 ECMO should no longer be considered a therapy of desperation, but instead part of our standard armamentarium for severe ARDS. 79 The decision to initiate ECMO in a patient with severe lung injury is difficult because we have limited data available to make a risk/benefit assessment, and the published data do not always reflect current clinical practice.…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
See 1 more Smart Citation
“…With simplification of ECMO technology we may no longer need 1:1 nurse/ECMO-specialist-to-patient ratio, which would improve resource allocation. 78 ECMO should no longer be considered a therapy of desperation, but instead part of our standard armamentarium for severe ARDS. 79 The decision to initiate ECMO in a patient with severe lung injury is difficult because we have limited data available to make a risk/benefit assessment, and the published data do not always reflect current clinical practice.…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…75 However, recent publications have reported survival rates over 70% in relation to ECMO for pediatric and adult patients with H1N1-influenza-induced ARDS. [76][77][78] Much has been learned from the over 45,000 patients in the Extracorporeal Life Support Organization registry. 75 Over the past decade, the technological advances in extracorporeal life support rival any other in the management of ARDS.…”
Section: Extracorporeal Membrane Oxygenationmentioning
confidence: 99%
“…4 Subsequently, in the northern hemisphere, many ICUs prepared to use ECMO as an option to face this pandemic. 17 20 was the only controlled clinical trial using modern ECMO technology. In this trial, 180 adults with severe respiratory failure were randomly assigned to continued conventional management or to referral to a specialized center with consideration for treatment with ECMO.…”
Section: Literature Reviewmentioning
confidence: 99%
“…72 With the simplification of ECMO systems we soon may no longer need a 1:1 nurse and ECMO specialist to patient staffing ratio, which would improve resource allocation. 73 Moving into the field of ethics, Dalton discussed the controversial use of ECMO for organ preservation. She clearly indicated that with regard to this application, ethical considerations have not yet caught up with technology.…”
Section: Ecmo: Moving At the Speed Of Lightmentioning
confidence: 99%